Development of Scholarship Information and Consultation Center Website for Straya Institute Using Prototyping Method - Faza Alliya Audristy Putri Ronce; Dwi Ratnasari; Santi Ika Murpratiwi (Journal of Computer Science and Informatics Engineering (J-Cosine), 2025)
The rapid development of information technology has had a considerable impact on the efficiency of education administration, especially in the management of scholarship information. However, many institutions still experience difficulties in handling data and limited access to scholarship information. The purpose of this research is to create a Scholarship Information and Consultation Center website for Straya Institute that can overcome these difficulties through prototyping. The prototyping approach allows for iterative development, ensuring that the system responds to user needs through continuous feedback and revision. The system is intended to facilitate access to scholarship information, program registration, and consultation with users. Evaluation methods include system testing using black-box testing and User Acceptance Testing (UAT), involving administrative and general users. The results showed a high level of user satisfaction (average UAT score of 98.2%), verifying the efficiency, usability, and usefulness of the system. This research advances the field by providing an effective digital solution for scholarship management, improving accessibility, and optimizing administrative operations. Future research could look at other enhancements such as automated scholarship file selection and AI-powered recommendation systems to improve user experience.